Simultaneous determination of vitexin and isovitexin in rat plasma after oral administration of Santalum album L. leaves extract by liquid chromatography tandem mass spectrometry. (15th June 2012) - Yan, Chong; Liu, Hongju; Lin, Li
ABSTRACT An LC‐MS/MS method was developed for the simultaneous determination of vitexin and isovitexin in rat plasma, using puerarin as the internal standard (IS). Plasma samples extracted with protein precipitation procedure were separated on a Diamonsil® C18 column (150 × 4.6 mm, 5 µm) with a mobile phase composed of methanol and 0.1% formic acid (45:55, v/v). The detection was accomplished by multiple reaction monitoring mode in positive electrospray ionization source. The optimized mass transition ion‐pairs for quantitation were m/z 431.2 → 311.1 for vitexin and isovitexin, and m/z 415.1 → 295.1 for IS. The total run time was 7.5 min for each injection. The calibration curves were linear (r2 > 0.99) over the investigated concentration range (2.00–2000 ng/mL) and the lower limits of quantification were 2.00 ng/mL in rat plasma sample. The intra‐ and inter‐day relative standard deviations were no more than 14.9% and the relative errors were within the range of −3.2–2.1%. The extraction recoveries for both compounds were between 89.3 and 97.3%. The robust LC‐MS/MS method was further applied in the pharmacokinetic study in Sprague–Dawley rats after oral administration of Santalum album L. leaves extract at a dose of 116 mg/kg. Copyright © 2012 John Wiley & Sons, Ltd.